Prevalence of AHPND in shrimp farms of the Nicoya Gulf and Central Pacific, Costa Rica - Peña-Navarro, Nelson (2024)
Introduction. The acute hepatopancreas necrosis disease (AHPND) is caused by bacteria Vibrio parahaemolyticus containing a plasmid encoding the toxin genes pirA and pirB. The disease is characterized by massive sloughing of epithelial cells in the hepatopancreas, also showing atrophy and discoloration of that organ. Diseased shrimp display anorexia with empty guts, weakness, body discoloration and high mortality. Objective. To determine the prevalence of Vibrio parahaemolyticus causing AHPND in farms that grow shrimp in the Pacific zone of Costa Rica. Materials and methods. During the years 2019 and 2020, water and shrimp (Penaeus vannamei) samples were obtained from 32 farms located on the western coast of the Nicoya Gulf (Northwest Costa Rica) and the Central Pacific coast (Puntarenas-Parrita). The samples were analyzed by endpoint polymerase chain reaction (PCR) using different protocols and primers to detect the toxins pirA and pirB. Further, a linear correlation between the presence of AHPND and water quality was done using the R statistical program. Results. The presence of Vibrio parahaemolyticus causing AHPND occurred in 93.75 % (30/32) of sampled ponds in both farming areas. Conclusion. This work confirms the presence and wide distribution of AHPND in water and shrimp from thirty shrimp farms in the Costa Rican Pacific.